The Impact of Interferon Lambda 3 Gene Polymorphism on Natural Course and Treatment of Hepatitis C. (27th August 2012) - Bellanti, F.; Vendemiale, G.; Altomare, E.; Serviddio, G.
Abstract : Host genetic factors may predict the outcome and treatment response in hepatitis C virus (HCV) infection. Very recently, three landmark genome-wide association studies identified single nucleotide polymorphisms near the interleukin 28B (IL28B) region which were more frequent in responders to treatment. IL28B encodes interferon (IFN) λ 3, a type III IFN involved in host antiviral immunity. Favourable variants of the two most widely studied IL28B polymorphisms, rs12979860 and rs8099917, are strong pretreatment predictors of early viral clearance and sustained viral response in patients with genotype 1 HCV infection. Further investigations have implicated IL28B in the development of chronic HCV infection versus spontaneous resolution of acute infection and suggest that IL28B may be a key factor involved in host immunity against HCV. This paper presents an overview about the biological activity and clinical applications of IL28B, summarizing the available data on its impact on HCV infection. Moreover, the potential usefulness of IFN λ in the treatment and natural history of this disease is also discussed.